Development of a minipig physical phantom from CT data. (28th July 2017) - Park, Sooyeun; Lee, Pilsoo; Ha, Wi-Ho; Kim, Han Sung; Park, Byeong Ryong; Kim, Jae Seok; Shim, Sehwan; Park, Sunhoo; Kim, Young-su; Kim, Chan Hyeong; Jin, Young-Woo
ABSTRACT: Quantification of pathological progression of radiation-induced injury is essential in development of treatment methods, and a proper animal model is necessary for relevant radiological and medical studies. A minipig is a current animal model selected because of its similarities to humans in anatomy and pathology. In the present study, a minipig physical phantom was developed using computed tomography (CT) data. For dosimetry purposes, the minipig physical phantom was constructed on a slice-by-slice basis, with an array of holes to accommodate dosimeters. The phantom is constituted of three major organs, i.e. bone, lung, and remaining soft tissue, and the organs are clearly distinguishable on each 20-mm-thick axial slice. The quality of the tissue-equivalent (TE) substitutes was analyzed in terms of the atomic compositions and Hounsfield units (HUs). The density (in g/cm 3 ) and effective atomic number of TE substitutes for the bone, lung, and soft tissue are 1.4 and 7.9, 0.5 and 10.0, and 1.0 and 5.9, respectively. Although the TE substitutes have slightly different physical properties, we think the phantom is acceptable because the HU values of the TE substitutes lie in the HU range of real tissues.